(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article analyzes the scholarly activity of American historian and orientalist S. Frederik Starr on Central Asia and its significance within the Western academic community. Drawing on Starr’s work Lost Enlightenment and other studies, the author examines the process of rediscovering the cultural, historical, and civilizational image of Central Asia in Western orientalism. The article evaluates Starr’s methodological approach, his contribution to Uzbek and Central Asian studies, and the role of these investigations in contemporary international academic discourse. The research employs comparative-historical analysis, textual analysis, and hermeneutic approaches. The findings aim to establish methodological foundations for the mutual enrichment of Uzbek and Western academic traditions.